Socioeconomic Factors Affecting Rural Households' Participation in Commercial Fuelwood Production in Jawi District, Northwest Ethiopia - Kassa Chanie; Mitku Alemu; Asabeneh Alemayehu; Abdulkerim Getachew; Mulat Ayal; Abebaw Shimeles (CV. Literasi Indonesia, 2025)
This study assesses the factors influencing household participation in fuelwood production in Jawi district, northwest Ethiopia. A multi-stage sampling method was used. The district and kebeles were purposefully selected. Snowball sampling techniques were employed to select fuelwood producers, while random sampling was used for non-producers. Data collection involved household questionnaires, key informant interviews, and focus group discussions. Binary logistic regression analysis was used to identify the determinants of household participation in fuelwood production. The results showed that the occurrence of crop pests, livestock holding size, total landholding size, distance from the homestead to the forest, institutional membership, education level of the household head, and total annual income are significant factors affecting participation. The study concludes and recommends that addressing crop pests, improving livestock productivity, creating alternative income sources, raising awareness, and promoting sustainable forest management through effective policies and stronger institutional frameworks can enhance rural livelihoods and help conserve natural forests.